Demographic, psychological and relationship factors are associated with resource loss among pregnant women - Costa, Eleonora C. V. (2019)
Objectives: This study analysed the association between demographic, psychological and relationship factors and resource loss in pregnant women. Methods: Quantitative descriptive correlational study. Depressive mood, social support, relationship intimacy and resource loss were assessed in a sample of 200 pregnant women recruited from public primary-care clinics. Results: Hierarchical regression showed that being younger, having lower yearly income, and having stronger depressive mood, little relationship intimacy and little satisfaction with social support were the main factors associated with resource loss. Depressive mood accounted for most resource loss after controlling for demographic risk factors. The models show the combined influence of demographic, psychological and relationship factors in shaping resource loss. Conclusions and implications: Depressive mood was a major risk factor for resource loss among pregnant women, whereas social support and relationship intimacy had a protective role. The results highlight the importance of screening for depressive mood and level of resources during routine prenatal care, in order to identify pregnant women at risk of depression. The findings point to interventions that foster patient's emotions to help them protect resources.